Inmediate loading in implantology - Allen Lengua, Cliflord (2005)
lnmediate funtional loading is a new surgical - prosthetic technique that can be used extensively in implant placement. Because of a lack of experimental reports regarding edentolous maxilla, we decided used this procedure it evaluate in the future.